Critical Review of Nursing Innovations in Emergency Care and Chronic Disease Management - Al Shamlan, Ali Bardan Mana; Almoyed, Abdullah Hasan; Almahboob, Neamah Saad Saeed Saad; Alshria, Sabra Hamad Mahdi; Al Htrash, Bashair Mohammed Awad; Al-Geshanien, Mahdi Makhfoor; Balhareth, Huda Abduilah Mohamad; Al Swar, Awad Musfer Masloom; Alfaraj, Abdullah Awadh; Almota, Mohmmed Hussin (Journal of Ecohumanism, 2024)
This paper critically reviews innovations in nursing practice within two essential domains of healthcare: aesthetics, acute & emergency care, and the treatment of chronic illnesses. The nursing profession has responded to the continuing expansion of these areas directed toward enhancing patients’ status, cost containment in the healthcare sector, and the general quality of care. In emergency care, innovations like the triage system, nurse-led emergency care, and the application of advanced technologies in assessing and managing emergency patients have revolutionized emergency care. Nursing in the care of chronic illness has described new roles in disease prevention, patient education, and chronic illness care with the use of new technologies and interventions to enhance the overall health of patients with chronic health conditions. This review looks at recent innovations in nursing, assesses their utility, and weighs their application to emergency and chronically ill patient populations or nursing.